BOTANICAL AND CHEMICAL COMPOSITION OF COMMON GRASS SPECIES AROUND DIP–TANK AREAS IN SEMI–ARID COMMUNAL RANGELANDS OF SWAZILAND - Solomon Tefera Beyene; Victor Mlambo (Tropical and Subtropical Agroecosystems, 2012)
Communal rangelands in arid and semi–arid areas of southern Africa are the source of virtually all feeds for wild and domestic ruminants. However, the quality and quantity of feed fluctuates in response to rainfall patterns. Little is known about the capacity of these rangelands to support ruminant productivity during the 4-month dry season. This study was therefore designed to assess the botanical composition of grasses and determine nutritive values of selected grass species growing in the communal rangelands of Swaziland at the start of the dry season. Vegetation survey and sampling were carried out in two semi–arid ecological zones (Lower Middleveld (LMV) and Lowveld (LV) savannas). Dry matter (DM), organic matter (OM), crude protein (CP), minerals, neutral detergent fibre (NDF) and acid detergent fibre (ADF) contents were determined. Of the 20 grass species identified in the two zones, 9 were perennials and 11 were annuals. Only 3 the grass species were classified as highly palatable. Grass species showed significant (P